Penerapan Pembelajaran Sejarah Menggunakan Museum Virtual Berbasis Zoom Meeting - Alqudsi, Zainab; Khasanah, Nurul Uswatun; Murtiyasa, Budi (Lembaga Yasin AlSys, 2023)
Every school system needs to moderate with technology that allows them to learn faster, better, and smarter. Information technology is the key to a better future school model. This study aims to explain and describe how the application of history learning using a virtual museum based on zoom meetings. The research subjects used were history teachers and class X students of Daarul Qur'an Karanganyar Science High School in the 2022/2023 academic year. The type of research used is descriptive qualitative with case study method. Collection technique is done by tri-angulation (combined). Data analysis is inductive or qualitative and research results. Instruments in this study researchers used the method of observation, interviews, and documentation. Learning history through a virtual museum at Daarul Qur'an Karanganyar Science High School has had a very positive impact. This is because the students at the Islamic boarding school are not allowed to use electronic devices and there is control over the time of daily activities so that these activities can increase the knowledge of the students and overcome distance, time and costs.